Some Medicinal Plants among the Tribes of Chhatarpur District (M.P.) India - Arjariya, Amita; Chaurasia, Kalpana (Ecoprint: An International Journal of Ecology, 2010)
The Chhatarpur District in central India is home to numerous herb species. The agro-climatic conditions prevailing in the region provide an ideal habitat for the natural growth of a variety of plants and herbs, which provide raw materials for pharmaceutical, phytochemical, food, flavoring and cosmetic industries. The paper provides information on 58 medicinal plants used by the Gond, Bhil and Bediya tribes of Chhatarpur district of Madhya Pradesh, India, for the treatment of various diseases. Traditional medicine remains an integral part of the health system in this area. Medicinal plants of forest origin hold great promise to enhance the health and livelihoods of the forest dwellers. Key words: Ethno medicinal, tribes, medicinal plants, traditional uses, diseases. DOI: 10.3126/eco.v16i0.3472 ECOPRINT 16: 43-50, 2009